City Information Modeling as a tool in urban management: application of GIS-BIM integration (Research, Society and Development, 2022)
Urban centers are becoming increasingly complex environments, causing changes that are expressed both in the city landscape and in people's behavior and lifestyle, thus causing transformations that directly impact the urban socio-spatial structuring. In this way, this paper presents part of the results of a master's research, with the objective of developing guidelines for the integration of GIS-BIM software, in order to facilitate decision making in urban planning. To this end, the Design Science Research (DSR) method will be used, using artifacts to solve real-world problems. It presents approaches for GIS-BIM integration, through the compatibility of georeferencing and modeling of a neighborhood in the city of Pau dos Ferros/RN - Brazil. As results, a proposal with guidelines for GIS-BIM integration was developed, and by applying it, it was possible to obtain the total modeling of the neighborhood with 1,496 modeled buildings, where the parameters of gauge, built area and projection area of the building can be extracted automatically. The development of this integration contributes to reducing the cost of time and resources to produce geographic information, as well as facilitating the visualization and understanding of the territory studied.